Mengungkap Fakta Pembatalan Hak Kepemilikan Tanah Berdasarkan Undang-Undang Nomor 5 Tahun 1960 - Ibrohim, Moh. (AKADEMIK: Jurnal Mahasiswa Humanis, 2021)
This thesis entitled: “(Certification of Property as a Tool Strong Evidence Can be declared null and void Due Certificate of Ownership Verification Tool Not As Seen From the Absolute Law No. 3 of 1999 on Basic Regulation of Agrarian”, Case Studies in Land Dispute Kelurahan Bintaro, Kecamatan Pesanggrahan, Kota Administrasi Jakarta Selatan)”, Frequent land disputes and disputes arising due to mafia soil, ultimately resulting in an actual loss to the legitimate owners of the land. The purpose of this paper is to present a study on land rights certificates pursuant to Law No. 3 of 1999, as strong evidence that can be canceled arguments premises stronger by others. The method used in this study is mainly empirical jurisdiction. Juridical empirical means to identify and conceptualize the law as a social institution and functional in real life systems are patterned. The data obtained from the research literature conducted the data analysis process-descriptive-analytic order to obtain a qualitative conclusion. The results of the study provide empirical evidence that the certificate of title for the land is not absolute evidence that publication cannot be undone, so for those who feel aggrieved may file a complaint with the Administrative Court as a legal institution that has authority in the issuance.